4D - New dimensions of open space use - Almási, Balázs; Báthoryné Nagy, Ildikó Réka (4D Journal of Landscape Architecture and Garden Art, 2006)
In our running-by world, there is a present demand towards revitalizing open spaces to meet the direct and indirect needs of information society. As we frequently use Virtual spaces we have a hard tiny to fully experience real spaces: rooms to calm down, to re-explore our physical environment and to reorganize classical human connections. New demands set questions to contemporary landscape architecture how to interchange position between the Virtual and physical, how to capture space-users’ attention and how to build-in the new dimensions to open space use.
Keywords: open space